TWO REMARKABLE LINDERA SPECIES (LAURACEAE) PROBABLY REPRESENTING AN UNDESCRIBED GENUS - AJGH Kostermans (BRIN Publishing (Penerbit BRIN), 1992)
Two species of Lindera (Lauraceae), on from Annam (Lindera spicata spec. nov.) an d one from Sulawesi, Indonesia (Lindera racemiflora spec. nov.) with unusual kind of inflorescence are described. Their genetic identity is not absolutely sure, as mature flowers are lacking. Ultimately they may belong to an undescribed genus.